SỰ PHÙ HỢP TRONG SỬ DỤNG THUỐC ĐIỀU TRỊ BỆNH TAY CHÂN MIỆNG (Vietnam Journal of Community Medicine, 2021)
Objective: To evaluate the appropriateness in using drugs of hand, foot and mouth disease treatment at the Children’s Hospital of Can Tho city in 2019. Subjects and methods: Retrospective cross-sectional descriptive study on 400 medical records of inpatients at Can Tho Children’s Hospital during the period from January 2019 to December 2019. Results: There was a statistically significant difference between the group of patients using the dose appropriate to the prescribed dose (P = 0.000